Bilateral Severely Stenotic Jugular Foramen: Diagnosis and Management from the Otologist/Neurotologist Point of View - Raquel Acinho Bento; David Rodrigues; João Levy; Tiago Eça; Vitor Oliveira; Leonel Luís (Case Reports in Otolaryngology)
Bilateral jugular foramen stenosis with jugular bulb and vein aplasia is rare in nonsyndromic craniosynostosis and usually diagnosed during childhood. We present a case of bilateral jugular foramen stenosis with jugular bulb and vein aplasia, with subsequent persistence and enlargement of the fetal venous anastomosis in the middle and posterior cranial fossa, along with a review of the literature about this anatomical abnormality, highlighting the surgical challenges and management from the otologist/neurotologist point of view.